A multifunctional subassembly of carbon nanotube paper for stable lithium metal anodes. (October 2022) - Wang, Muqin; Ren, Zhongmin; Chen, Zhenlian; Lin, Huan; Yan, Jingkun; Lu, Zhaoxin; Chen, Shuaishuai; Li, Hua; Shen, Yan; Xie, Ming; Wang, Mingkui; Wang, Deyu
Abstract: Uncontrolled lithium growth and the consequent interfacial reaction are obstacles to the practical application of lithium metal anode. Here, a multifunctional subassembly of carbon nanotube paper grafted with a thin layer of LiNO3 (LNO@CP) is proposed. According to the results of experiments and theory calculation, the nucleation sites are enriched and the nuclei are tailored into spherical shape on LNO@CP. Consequently, the Li plating gradually fills the void of LNO@CP and then grows outward uniformly, resulting in an increased Li reversibility and a stable solid electrolyte interphase layer. The LNO@CP covering the Li backup source works as a protective layer to defense the electrolyte corrosion effectively. The lithium metal battery with this multifunctional subassembly delivers a remarkable capacity retention of 81.2% after 500 cycles. This work emphasizes that the a protective layer such as LNO@CP is crucial to the high performance lithium metal battery. Graphical abstract: Image 1 Highlights: The lithium (Li) affinity of carbon nanotube paper (CP) is improved by grafting LiNO3 onto its surface. The CP with LiNO3 (LNO@CP) enriches the Li nucleation sites, resulting in the Li filling into the void space of CP and the outward controllable Li growth. The LNO@CP also works as a protective layer on Li metal anode to defense electrolyte corrosion. All the merits endow the Li metal batteries with LNO@CP with an excellent capacity retention of 81.2% after 500 cycles.